Company Policies in Indonesia in Overcoming Employee Compensation and Job Satisfaction During the Covid-19 Pandemic Period - Riyan M. Faris; Nira Aktaviana; Amdan Firmansyah; Dinda Apriliani (Nusantara Science and Technology Proceedings, 2020)
Introduction: Compensation is all benefits/results of work received by an employee for the results of his work, either directly or indirectly. Job Satisfaction is a feeling that is described as feeling happy (satisfied) with what employees get from the company. Corona or Covid-19 is a new type of virus (SARS-CoV-2). The development of the coronavirus has hit various sectors, especially the economic sector. The Covid-19 pandemic problem appears to be affecting employee compensation and job satisfaction in the workplace because employees are forced to work differently from working in offices. The purpose of the literature review is to find out how the conditions of compensation and job satisfaction of employees and companies in Indonesia during the Covid-19 pandemic. Method: Literature Review. Of the 8 studies used, 8 of them used quantitative research methods. The population is all employees in various companies and the samples used are some employees who work in companies in Indonesia and some employees of various companies in the world. Results: Based on 8 studies, it was found that Employee Compensation and Job Satisfaction from company policies during the Covid-19 Pandemic was quite decreasing. Because compensation does not significantly increase and even decreases, employee job satisfaction also decreases which can come from the extent to which people like or dislike their work. Discussion: Compensation and Job Satisfaction for employees provided by the company during the Covid-19 Pandemic is a problem that must be studied and found a solution so that employee performance remains good and quality.